Pair-Coding as a Method to Support Intercoder Agreement in Qualitative Research - Paul, Jeffrey W.; Rodrigues, Renato Bezerra; Cicek, Jillian Seniuk (Proceedings - Frontiers in Education Conference, 2021)
The goal of this WiP paper is to provide an overview of our adaptation of pair programming from agile software development to support intercoder agreement in qualitative analysis. In pair programming, two programmers work together on the same program: one writes while the other observes and guides. Pair programming interleaves development and inspection activities and has been shown to produce higher quality software in a shorter time than individuals working alone. Our adaptation of agile software development pair programming to qualitative research, which we have called pair-coding, uses a similar approach to merge the qualitative research activities of coding and consensus-building by having two team members work on the same text simultaneously. In using pair-coding in qualitative research, the active team member highlights passages and assigns codes while the other team member observes and guides. Our research team anecdotally found that pair-coding of qualitative data provided benefits that were similar to the benefits of pair programming. Specifically, consensus and consistency were built continuously rather than at discrete stages. As well, differences in biases and worldviews were overtly revealed in the act of coding, thus improving the bracketing of biases. Finally, we found that consensus was better understood when built in the moment of coding rather than in comparison after the fact. We believe pair-coding could be effective in supporting the trustworthiness and credibility of qualitative analysis.